2010
DOI: 10.1002/jbm.b.31679
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and evaluation of a biodegradable cohesive plug based on reconstituted collagen/γ‐polyglutamic acid

Abstract: In the past decade, numerous studies have been devoted to developing natural bioadhesives that have the notable capacity to adhere to wet surfaces. Collagen and γ-polyglutamic acid (γ-PGA) are well-known natural hydrophilic polymers that have both been utilized for their versatility in a wide range of biomedical applications. The aim of this study was the construction and characterization of a cohesive plug composed of γ-PGA and reconstituted collagen fibrils crosslinked with water-soluble carbodiimide. Transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…It has seen some application in soft tissue engineering within cross‐linked hydrogels . Attempts to equip this polyamide with characteristics suited to tissue engineering have been based on blending with natural (collagen and chitosan) and synthetic polymers (PLA, PLGA, and PCL) however, research has been limited due to the low availability of γ ‐PGA.…”
Section: Naturally‐occurring Polymersmentioning
confidence: 99%
“…It has seen some application in soft tissue engineering within cross‐linked hydrogels . Attempts to equip this polyamide with characteristics suited to tissue engineering have been based on blending with natural (collagen and chitosan) and synthetic polymers (PLA, PLGA, and PCL) however, research has been limited due to the low availability of γ ‐PGA.…”
Section: Naturally‐occurring Polymersmentioning
confidence: 99%
“…This periodicity, or D-banding pattern, ranges from 64 to 67 nm, depending on the tissue or organ . The D-pattern is reported to be important for several cellular and biological processes such as bone matrix mineralization, cell morphology, and hemostasis. Bone mineral crystals first form in the gaps of the collagen fibrils . The gap interface has been associated with primary mineralization events in the early stages of in vivo bone formation .…”
Section: Introductionmentioning
confidence: 99%
“…The number of cells increased with increasing kebab crystal size. 28 So, 0.5 wt % PCL solution was applied to form SK structure in this study. SEM images (Figure 2c,d) showed the periodic kebab pattern covering the whole nanofiber, which is consistent with the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, different concentrations of PCL solution (0, 0.01, 0.05, 0.1, and 0.5 wt %) were applied to form kebab crystals on nanofibers, and it was found that the kebab crystals became larger with increasing concentration of PCL solution. The number of cells increased with increasing kebab crystal size . So, 0.5 wt % PCL solution was applied to form SK structure in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation